Overexpression of Salusin-α Inhibits Vascular Intimal Hyperplasia in an Atherosclerotic Rabbit Model. (12th July 2018) - Qian, Kun; Feng, Li; Sun, Yujie; Xiong, Bowen; Ding, Yi; Han, Panting; Chen, Hailun; Chen, Xiao; Du, Ling; Wang, Yuxue
Abstract : Inhibiting vascular endothelial foam is the focus of clinical attention. Using SonoVue (an ultrasound contrast agent), the salusin- α gene was transfected into the arterial intima of an atherosclerotic rabbit model induced by a high-fat diet in this study. Subsequently the model of blood lipid indexes, the pathological structure of the intima, and changes in molecules regulating atherosclerosis were investigated. The high-density lipoprotein C and apolipoprotein A values in the salusin- α gene overexpression (P) group were higher than those in the salusin- α gene interference (RP) group ( P < 0.05), whereas the total cholesterol, low-density lipoprotein C, and apolipoprotein B values were reversed. Rabbits in the P group showed significantly thinner vascular intimal thickness than that of other experimental groups ( P < 0.05). The expression of positive regulators of atherosclerosis ( ABCA1, ABCG1 ) was higher in the P group than that in the RP group ( P < 0.05), and the opposite effect was observed for negative regulators ( ACAT1, CD36 ). Thus, our results showed that the overexpression of salusin- α gene inhibited the proliferation of the vascular intima, thereby throwing some light on understanding the mechanism how salusin- α gene expression interfered with the foaming of vascular intimal cells.